2009
DOI: 10.1159/000226233
|View full text |Cite
|
Sign up to set email alerts
|

Extensive IgE Cross-Reactivity towards the Pooideae Grasses Substantiated for a Large Number of Grass-Pollen-Sensitized Subjects

Abstract: Background: Allergy to taxonomically related species is a common phenomenon caused by the same immunological receptor cross-reacting to homologous allergens from different species. Knowledge of patterns of cross-reactivity is crucial for the selection of optimal products for diagnosis and for specific immunotherapy. The objective of this study was to investigate patterns of serum IgE cross-reactivity towards pollens from various grass species. Methods: With grass group 1 allergens as the representative group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 59 publications
4
50
0
1
Order By: Relevance
“…28,29 However, it has been shown that more than 90% of the IgE sensitization against grass pollen can be measured by using this representative allergenic source. 30 Fifth, some of the components of P pratense (eg, Phl p 4) might be less clinically relevant than others, although additional clinical data have been claimed to reach a firm conclusion on this point. 31 On the other hand, sensitization to Phl p 7 (polcalcin) and Phl p 12 (profilin) might have been induced by other pollen sources carrying cross-reactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 However, it has been shown that more than 90% of the IgE sensitization against grass pollen can be measured by using this representative allergenic source. 30 Fifth, some of the components of P pratense (eg, Phl p 4) might be less clinically relevant than others, although additional clinical data have been claimed to reach a firm conclusion on this point. 31 On the other hand, sensitization to Phl p 7 (polcalcin) and Phl p 12 (profilin) might have been induced by other pollen sources carrying cross-reactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the exact Pooideae member inducing primary sensitization may not be as important; both mixed grass pollen extracts and single representative species ( P. pratense pollen) have been argued to be effective [22,23,24,25]. …”
Section: Markers Of Genuine Sensitization To Major Pollen Sourcesmentioning
confidence: 99%
“…The LTP, which can cross-react with LTP from several other plants [24,25], could be present in the barley kernel surviving the malting and brewing process [18]. Beer LTP can be found intact in the beer as one of its main protein components.…”
Section: Discussionmentioning
confidence: 99%